Machine Learning on Graph-Structured Data - Barros, Claudio D. T.; da Silva, Daniel N. R.; Porto, Fabio A. M. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2021: Anais Estendidos do XXXVI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2021.18179, 2021)
Several real-world complex systems have graph-structured data, including social networks, biological networks, and knowledge graphs. A continuous increase in the quantity and quality of these graphs demands learning models to unlock the potential of this data and execute tasks, including node classification, graph classification, and link prediction. This tutorial presents machine learning on graphs, focusing on how representation learning - from traditional approaches (e.g., matrix factorization and random walks) to deep neural architectures - fosters carrying out those tasks. We also introduce representation learning over dynamic and knowledge graphs. Lastly, we discuss open problems, such as scalability and distributed network embedding systems.